Archives of dispossession : recovering the testimonios of Mexican American herederas, 1848-1960 - Roybal, Karen R. (Gender & American culture., 2017)
"One method of American territory expansion in the U.S.-Mexico borderlands was the denial of property rights to Mexican land owners. Many historical accounts overlook this colonial impact on Indigenous and Mexican peoples, and what existing studies do tackle this subject tend to privilege the male experience. In Archives of Dispossession, Karen Roybal recenters the focus of land dispossession on women, arguing that gender, sometimes more than race, dictated legal concepts of property ownership and individual autonomy. Drawing on a diverse source base - legal land records, personal letters, and literary works - Roybal reveals voices of Mexican women in the Southwest and how they fought against the erasure of their rights, both as women and as Indigenous landowners. Woven throughout Roybal's analysis are these women's testimonies - their stories focusing on inheritance, property rights, and sovereignty. Roybal positions these testimonios as an alternate archive that illustrates the myriad ways in which multiple layers of dispossession - and the changes of property ownership in Mexican law - affected the formation of Mexicana identity"--